Simultaneous measurement of total Estradiol and Testosterone in human serum by isotope dilution liquid chromatography tandem mass spectrometry - Zhou, Hui (Anal Bioanal Chem, 2017)
Reliable measurement of total testosterone and estradiol is critical for their use as biomarkers of hormone related disorders in patient care and translation research. We developed and validated a mass spectrometry method to simultaneously quantify these analytes in human serum without chemical derivatization. Serum is equilibrated with isotopic internal standards and treated with acidic buffer to release hormones from their binding proteins. Lipids are isolated and polar impurities are removed by two serial liquid-liquid extraction steps. Total testosterone and estradiol are measured using liquid chromatography tandem mass spectrometry (LC-MS/MS) in combination of positive and negative electrospray ionization modes. The method shows broad analytical measurement range for both testosterone 0.03–48.5 nM (0.75–1400 ng/dL) and estradiol 11.0–5138 pM (2.99–1400 pg/mL) and excellent agreement with certified reference materials (mean bias less than 2.1% to SRM 971, BCR 576, 577, and 578) and a high order reference method (mean bias 1.25% for testosterone and −0.84% for estradiol). The high accuracy of the method was monitored and certified by CDC Hormone Standardization (HoSt) Program for two years with mean bias −0.7% (95%CI: −1.6% to 0.2%) for testosterone and 0.1% (95%CI: −2.2% to 2.3%) for estradiol. The method precision over a 2-year period for Quality Control pools at low, medium and high concentrations was 2.7–2.9% for testosterone and 3.3–5.3% for estradiol. With the consistently excellent accuracy and precision, this method is readily applicable for high-throughput clinical and epidemiological studies.